2014
DOI: 10.20360/g2zk5x
|View full text |Cite
|
Sign up to set email alerts
|

Singing is a Celebration of Language: Using Music to Enhance Young Children’s Vocabularies

Abstract: Music engages children in language learning, offering them opportunities to understand and express their ideas and communicate with others in ways that go beyond words. This article, based on two ethnographically-framed studies and the use of two real-life vignettes, demonstrates how singing and musical experiences (e.g., composition, soundscapes, musical improvisation) have the power to enhance children's lexical acquisition and semantic knowledge at various levels of development. Results demonstrate that sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…“Music is an excellent pedagogical partner” (Montgomery and Smith, , p. 29) is the generalised sentiment in much of the literature for the teaching of early pre‐reading skills, as it has been found to help increase phonemic and phonological awareness (Hansen and Milligan, ). Early literacy researchers have also cited singing as beneficial to the acquisition of print literacy given that singing is said to “encourag[e] oral language skills, physical development, and an understanding of concepts such as sequence and patterning” (Connors, , p. 22), broaden vocabulary development and “enhance children's lexical acquisition and semantic knowledge” (Winters and Griffin, , p. 78). Pairing music and print within song‐based picture books has also been shown to support children's oral language and concepts of print (e.g., Barclay, ), while musical prosody (i.e., “the complex interrelationships of rhythm … and pitch” (Gabriel and Countryman, , p. 45)) has been shown to support reading fluency and enhance reading programmes (Frasher, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…“Music is an excellent pedagogical partner” (Montgomery and Smith, , p. 29) is the generalised sentiment in much of the literature for the teaching of early pre‐reading skills, as it has been found to help increase phonemic and phonological awareness (Hansen and Milligan, ). Early literacy researchers have also cited singing as beneficial to the acquisition of print literacy given that singing is said to “encourag[e] oral language skills, physical development, and an understanding of concepts such as sequence and patterning” (Connors, , p. 22), broaden vocabulary development and “enhance children's lexical acquisition and semantic knowledge” (Winters and Griffin, , p. 78). Pairing music and print within song‐based picture books has also been shown to support children's oral language and concepts of print (e.g., Barclay, ), while musical prosody (i.e., “the complex interrelationships of rhythm … and pitch” (Gabriel and Countryman, , p. 45)) has been shown to support reading fluency and enhance reading programmes (Frasher, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though print literacy may be at the forefront of the above literature, some of this work has also suggested that singing has additional potential for people's meaning making. Winters and Griffin (), for instance, have argued that when print literacies and music intersect, communication opportunities change: “Music engages children in language learning, offering them opportunities to understand and express their ideas and communicate with others in ways that go beyond words” (p. 78). Building on the work of Small (), Gabriel and Countryman () found that the process of musicking , “singing, playing, moving and listening to music” provides children with openings “for exploring the nature of relationships (both sound relationships and people relationships)” (p. 43) that can be emotionally evocative (Frith, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of AI programs has been effective across the PreK-12 continuum. Four studies described the effectiveness of AI in preschools (Brown & Sax, 2012;Cremin et al, 2015;Phillips et al, 2013;Winters & Griffin, 2014). Twenty studies illustrated how AI in science benefit students and teachers in elementary schools (Baker, 2013;Brouilette & Jennings, 2010;Cremin et al, 2015;Duma & Silverstein, 2014;Hardiman et al, 2014;Hendrix et al, 2012;Jakobson & Wickman, 2015;Klopp et al, 2014;Liu & Lin, 2014;Luftig, 2000;Lynch, 2007;Marshall, 2016;Nelson & Norton-Meier, 2009;Overton, 2004;Poldberg et al, 2013;Rufo, 2016;Scholes & Nagel, 2012;Stellflue, Allen, Gerber, & Boody, 2005;Webb & Rule, 2012).…”
Section: Age/grade Study Focusmentioning
confidence: 99%